Migrasi Kepada Penyedia Jasa Baru: Studi Intensi Berpindah Pelanggan Jasa Telepon Seluler - Wibowo, A.J. Ibnu (Jurnal Administrasi Bisnis, 2008)
A reasonably strong competitive atmosphere can now be felt among service provider of telecommunication industry, especially GSM mobile phones. Therefore, it is no doubt crucial for service provider of cell phone to possess profound understanding on why one client stay with one provider or leave them to move to another. The purposes of this research are to know whether there are any positive effects of push and pull factors to the clientsâ intention to migrate; and the negative effects of mooring factors to peopleâs attitude to do so. Furthermore, this research also discusses whether there are any negative effects of mooring factors to the relationship between push effects and clientsâ intention to migrate. Likewise the drawbacks of mooring effects related to the pull effects and clientsâ intention to migrate. This research is conducted among 230 economic students of Economic Faculty of University of Indonesia who have used GSM cell phone providers for at least six months. Most of the result obtained from this research supported the idea that there is a negative effect of mooring factors to the intentions to migrate. On the other hand, the data does not approve that there is a positive effect of push and pull factors to clientâs intention to migrate. Neither, in addition, do they support the notion that there is a negative effect of mooring effects towards relationship between pull effects and peopleâs intention to migrate. Later it is found that no significant negative effect of mooring effects towards relationship between pull effects and intention to migrate is found. Keywords: switching intentions, push effects, pull effects, mooring effects